1995
DOI: 10.1002/j.1552-4604.1995.tb05013.x
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin and Serotonin Antagonism in Cardiovascular and Non‐Cardiovascular Disease

Abstract: Serotonin, or 5-hydroxytryptamine, is a naturally-occurring vasoactive substance found primarily in the brain, enterochromaffin tissue, and blood platelets. It has diffuse cardiophysiologic effects. The multiple effects of serotonin on blood vessels can be explained by the existence of 2 serotonergic receptor subtypes (the S1 receptor mediates vasodilation, and the S2 receptor vasoconstriction). Serotonin via the S2 receptor also augments the actions of several other vasoconstricting substances. Serotonin may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
2
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 146 publications
0
35
2
1
Order By: Relevance
“…As the LV filling decreases, there is less systemic cardiac output, and this was observed in the MCT-induced PAH rats that became systemically hypotensive. Contrary to previous reports with the 5HT2A receptor blocker ketanserin, which caused systemic hypotension (Frishman et al, 1995;Frishman and Grewall, 2000), our experiment demonstrated no significant change in the LV pressure between the treatment groups and the PBS controls, suggesting less peripheral vasodilatation with more selective vasodilatation of the pulmonary vasculature.…”
Section: Discussioncontrasting
confidence: 99%
“…As the LV filling decreases, there is less systemic cardiac output, and this was observed in the MCT-induced PAH rats that became systemically hypotensive. Contrary to previous reports with the 5HT2A receptor blocker ketanserin, which caused systemic hypotension (Frishman et al, 1995;Frishman and Grewall, 2000), our experiment demonstrated no significant change in the LV pressure between the treatment groups and the PBS controls, suggesting less peripheral vasodilatation with more selective vasodilatation of the pulmonary vasculature.…”
Section: Discussioncontrasting
confidence: 99%
“…Pharmacological studies have revealed several subtypeselective agents: for example, 5-methylurapidil, KMD-3213, RS-17053 and nigludipine for the a1a-subtype (6 -9); spiperone for the a1b-subtype (10); and BMY7378 for the a1d-subtype (11, 12). Among them, 5-methylurapidil, spiperone and BMY7378 were originally categorized in serotonin (5-HT) receptor agonists and / or antagonists.Many 5-HT receptor antagonists have been developed and some of them are now clinically used as anticoagulants, antihypertensive drugs and antipsychotic drugs (13,14). Such therapeutic diversity of 5-HT antagonists may be related to their wide spectrum for not only 5-HT receptor family but also for heterogeneous receptors such as dopamine receptors and a1-adrenoceptors (15, 16).…”
mentioning
confidence: 99%
“…Many 5-HT receptor antagonists have been developed and some of them are now clinically used as anticoagulants, antihypertensive drugs and antipsychotic drugs (13,14). Such therapeutic diversity of 5-HT antagonists may be related to their wide spectrum for not only 5-HT receptor family but also for heterogeneous receptors such as dopamine receptors and a1-adrenoceptors (15, 16).…”
mentioning
confidence: 99%
“…In the vascular system, multiple effects of 5-HT are mediated primarily by 5-HT 1 and 5-HT 2 receptors. 16 5-HT induces VSMC proliferation, contraction, migration, and platelet aggregation. [17][18][19][20][21][22] 5-HT also participates in vascular inflammation associated with atherosclerosis.…”
mentioning
confidence: 99%